EFL STUDENTS' STRATEGIES DEALING WITH COMMON DIFFICULTIES IN TOEFL READING COMPREHENSION SECTION - Samad, Iskandar Abdul; Jannah, Miftahul; Fitriani, Siti Sarah (International Journal of Language Education, 2017)
TOEFL has been used as a requirement for non-native English students to pursue further study overseas, to get an appropriate job and to graduate from university. Students often encounter difficulties completing TOEFL reading test. This quantitative study investigates the undergraduate students’ difficulties and their strategies in completing TOEFL reading comprehension test. The data was obtained by collecting students’ worksheets of the TOEFL test and distributing questionnaires related to test taking strategies used by the students. Thirty students of English Education Department of Syiah Kuala University were involved as participants. The results indicate five difficult reading aspects encountered by the students. In addition, their strategies to complete the reading comprehension section of the TOEFL test are also found. These findings are further discussed in this paper.